Exodus immigration and Multiculturalism in the 21st Century - Collier, Paul. (London Penguin, 2014)
Exodus is an insightful, expert foray into the explosive issue of immigration, from paul collier, award-winning economist and author of the bottom billionmass international migration is a response to extreme global inequality, and immigration has a profound impact on the way we live. Yet our views - and those of our politicians - remain caught between two extremes: popular hostility to migrants, tinged by xenophobia and racism; and the view of business and liberal elites that 'open doors' are both economically and ethically imperative. With migration set to accelerate, few issues are so urgently in need of dispassionate analysis - and few are more incendiary.here, world-renowned economist paul collier seeks to defuse this explosive subject. Exodus looks at how people from the world's poorest societies struggle to migrate to the rich west: the effects on those left behind and on the host societies, and explores the impulses and thinking that inform western immigration policy. Migration, he concludes, is a fact, and we urgently need to think clearly about its possibilities and challenges: it is not a question of whether migration is good or bad, but how much is best?'exodus is an important book and one i have been waiting to read for many years ... [it is] a work that is humane and hard-headed about one of the greatest issues of our times' - david goodhart, sunday times'paul collier is one of the world's most thoughtful economists. His books consistently illuminate and provoke. Exodus is no exception' - economist'tinged with poignancy ... A humane and sensible voice in a highly toxic debate' - colin kidd, guardianpaul collier is professor of economics and director of the centre for the study of african economies at oxford university and a former director of development research at the world bank.
Includes index
Keywords: Immigration